Ukuran Benih Dan Skarifikasi Dengan Air Panas Terhadap Perkecambahan Benih Pohon Kuku (Pericopsis Mooniana) - Anita Luksi Indria Sandi; Indriyanto Indriyanto; Duryat Duryat (Jurnal Sylva Lestari, 2014)
Nedun tree (Pericopsis mooniana) is one of commercial trees. The propagation of nedun tree generatively has an obstacle due to it's dormant character and the variety of seeds weight and the both factors are suspected influence the germanitaion. This research aimed to determine effect of seed weight for nedun seed germination and the best of seeds weight for nedun seed germination; the effect of soaking in hot water at beginning temperature 80oC by different soaking period on germination, and the best effect of soaking in hot water at beginning temperature of 80oC by different soaking period on germination. This research was compiled in a randomized complete block design, with 5 treatments and 3 groups. Seeds were catagorized in to three group of weight which were heavy, medium, and light. The treatments consisted of without scarification (as a control), soaking in hot water at beginning temperature of 80ºC during 12 hours, 24 hours, 36 hours, and 48 hours. Every experiment unit consisted of 100 seed. The observed variables were consisted of germination percentage, mean daily germination, germination value, and the ability to germinate. Data analysis methods were used variance homogenity, variance analysis and least of difference test at 5% significant level. Based on the analysis of variance showed that seeds weight significantly affected the mean daily germination, but had no effect on germination percentage, germination value, and the ability to germinate. Seeds weight had a mean daily germination 15,088 days to germinate. The medium seeds were germinated faster than heavy seeds and light seeds. Seed scarification gave effect on germination percentage and germination value significantly, but not significant on mean daily germination and ability to germinate. Seeds scarification with hot water at beginning temperature 80°C for 48 hours had germination percentage 28,000%, germination percentage was better than the scarification for 36 hours, 24 hours, 12 hours, and control. Keywords: Pericopsis mooniana, scarification, seed size